Parallel Discourses Religious Identity and HIV Prevention in Botswana. - Jensen, Kipton E. (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
Animated by the belief that public health programs in Botswana, or other parts of sub-Saharan Africa, would be more effective if those who designed and implemented them possessed a better understanding of existing ethno-medical as well as religious beliefs and cultural practices, Parallel Discourses provides a revised topology of religious identity in Botswana and then shows why it is important to disaggregate or otherwise distinguish between diverse faith-based communities - from traditional ...
TABLE OF CONTENTS; LIST OF FIGURES AND TABLES; PREAMBLE; ACKNOWLEDGEMENTS; INTRODUCTION; CHAPTER ONE; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; CHAPTER FIVE; CHAPTER SIX; CHAPTER SEVEN; APPENDIX; ENDNOTES; BIBLIOGRAPHY.
Description based on print version record.
Keywords: AIDS (Disease) -- Botswana -- Prevention; AIDS (Disease) -- Botswana -- Prevention; HEALTH & FITNESS / Diseases / AIDS & HIV; MEDICAL / AIDS & HIV; Electronic books